2017
DOI: 10.1007/978-3-319-57168-3
|View full text |Cite
|
Sign up to set email alerts
|

Race, Gender, and Religion in the Vietnamese Diaspora

Abstract: The early modern period was witness to an incipient process of transculturation through exploration, mercantilism, colonization, and migration that set into motion a process of globalization that continues today. The purpose of this series is to bring together a cultural studies approachwhich freely and unapologetically crosses disciplinary, theoretical, and political boundaries-with early modern texts and artefacts that bear the traces of transculturalization and globalization in order to deepen our understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In doing so, Tweed argues that they transpose the conditions of displacement into survival and aspirations, reinterpreting their experiences of exile as hope and envisioning a future when they would return to Cuba. Other studies of Catholic immigrants in the US have found similar patterns of ethnic orthodoxy at local and global levels (Castañeda-Liles 2018;Ninh 2017;Horsfall 2000;Duricy 2008).…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…In doing so, Tweed argues that they transpose the conditions of displacement into survival and aspirations, reinterpreting their experiences of exile as hope and envisioning a future when they would return to Cuba. Other studies of Catholic immigrants in the US have found similar patterns of ethnic orthodoxy at local and global levels (Castañeda-Liles 2018;Ninh 2017;Horsfall 2000;Duricy 2008).…”
Section: Introductionmentioning
confidence: 60%
“…Meanwhile, the US has not fully integrated Vietnamese Catholics and Caodaists as citizens. Even though religious diversity and freedom is a fundamental right in American society, religion has become the proxy through which Vietnamese refugees are marginalized to the fringes of society as ethnic racial minorities (Ninh 2017). As Catholics, they have been racialized in American society as ethnically unrepresentative of Catholicism or not being "truly Catholic" because they are Asians practicing a "Western" religion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reinterpreted statues have become common diplomatic gifts exchanged between Vietnamese Catholic communities in different countries. In 2002, six of them were blessed by Pope John Paul II and distributed to Vietnamese Catholic communities on six different continents, and by 2010 Our Lady of LaVang has become a de facto symbol of the global Vietnamese Catholic diaspora (Ninh 2017).…”
Section: Our Lady Of Lavang As Online Proxymentioning
confidence: 99%
“…Although the practice of Ðạo Mẫu was officially recognized as the world's intangible cultural heritage by The United Nations Educational, Scientific and Cultural Organization (UNESCO) in 2016, many aspects of this Vietnamese religion are largely neglected, for instance, one of its major worshipping places called Ðiện thờ Mẫu tư gia (MGW private shrine/private temple). Some scholars mention Ðiện thờ Mẫu tư gia in their work as a way of acknowledging this unique worshipping place of Ðạo Mẫu; however, they do not provide any details on it (Fjelstad Nguyen 2006, 2011; Thien-Huong T. Ninh 2017). Even in the latest published articles and monographs, scholars do not include private shrines while naming the various places of worship of Ðạo Mẫu (Vũ and Phạm 2018;Phúc Hữu Nguyễn 2022) 2 .…”
Section: Introductionmentioning
confidence: 99%